Ideals of counterculture in 1960s songwriting - Černohousová, Lada (Univerzita Pardubice, 2018)
This thesis deals with 1960s counterculture and its ideals in songwriting. In the theoretical part, the term counterculture is explained, as well as important moments of the decade. This knowledge is then used in the practical part, where lyrics of songs from the 1960s are analysed.
Ideály alternativní kultury v písňové tvorbě 60. let
Keywords: music; counterculture; United States of America; 1960s; hudba; kontrakultura; Spojené státy americké; 1960